Treatment of multiresistant gram negative ventriculitis with intraventricular ciprofloxacin - (:unkn) unknown (My University, 1998)
Central nervous system infection remains an important cause of mortality and morbidity in patients with open spinal dysraphism. Two cases of myelochisis with multiresistant Klebsiella Ventriculitis were treated with intraventricular ciprofloxacin for persistently positive CSF cultures after commencement of iv quinolone treatment. The patients were cured both clinically and microbiologically. No significant adverse effects were observed in any of these patients.